KOMPOZITOR NAJIMADDIN MUXAMMEDDINOV DÓRETIWSHILIGINDE SIMFONIYALÍQ POEMA JANRÍ - Abatbaeva, R.A. (SCIENCE and SOCIETY, 2023)
This article examines the genre of the symphonic poem in the life of symphonic music in the countries of Central Asia in the 19th-20th centuries. The formation of Western musical culture and the emergence of various examples in the works of composers of Uzbekistan and Karakalpakstan. Thus, information is given on the analysis of the poem “Posqan el”, created in the symphonic genre by composer N. Muhammeddinov.